DNA‐organic molecular amphiphiles: Synthesis, self‐assembly, and hierarchical aggregates. Issue 4 (24th June 2021) - Zhao, Zhiyong; Dong, Yuanchen; Duan, Zongze; Jin, Dou; Yuan, Wei; Liu, Dongsheng
Abstract: With the development of deoxyribonucleic acid (DNA) nanotechnology, various DNA nanostructures and DNA devices have been constructed, which exhibit potential applications in material science and biomedicine. Taking advantage of the programmability and biocompatibility of DNA, novel building block to chemically functionalize DNA with hydrophobic organic molecules has attracted more and more attention. Driving by amphiphilicity, DNA‐organic molecular amphiphiles have been demonstrated to self‐assemble or further induce hierarchically assemblies, providing novel‐specific properties. In this minireview, we summarize the recent progress of DNA organic molecular amphiphiles including their synthesis, self‐assembly behavior in aqueous solution, and the amphiphilic self‐assembly based on hierarchical DNA nano‐structures. We further briefly discuss the perspective of the application of the DNA‐organic molecular amphiphiles. Abstract : DNA‐organic molecular amphiphiles are synthesized from hydrophilic DNA and hydrophobic organic molecules with various topologic structures. These DNA amphiphiles can self‐assemble into the designable nanostructures as well as induce the formation of the hierarchical aggregates.